Recent Progress in the Copper-Catalyzed Cascade Cyclization Involving Intramolecular Hydroamination of Terminal Alkynes - Tan, Tong-De; Chen, Yang-Bo; Fan, Xin-Yang; Ye, Long-Wu (Synlett, 2019)
Transition-metal-catalyzed cascade cyclization initiated by intramolecular alkyne hydroamination has received considerable attention over the past decade and has been widely used in the rapid construction of a diverse array of valuable complex N-heterocycles. Recent progress in this area is reviewed with an emphasis on the cheap and environmentally benign copper-catalyzed cascade cyclization of terminal alkynes.
Keywords: copper catalysis; hydroamination; alkynes; cascade reactions; cyclization; heterocycles